Increased Flame Retardancy of Enzymatic Functionalized PET and Nylon Fabrics via DNA Immobilization - Quartinello, Felice; Kremser, Klemens; Vecchiato, Sara; Schoen, Herta; Vielnascher, Robert; Ploszczanski, Leon; Pellis, Alessandro; Guebitz, Georg M. (Frontiers in Chemistry, 2019)
Poly(ethylene terephthalate) (PET) and nylon find their main applications in working clothes, domestic furniture and as indoor decoration (curtains and carpets). The increasing attention on healthy lifestyle, together with protection and safety, gained a strong interest in today’s society. In this context, reducing the flammability of textiles has been tackled by designing flame retardants (FRs) able to suppress or delay the flame propagation. Commercially available FRs for textiles often consist of brominated, chlorinated and organo-phosphorus compounds, which are considered a great concern for human health and for the environment. In this study, Deoxyribose Nucleic Acid (DNA) was investigated as a green and eco-friendly alternative to halogen-containing FRs. DNA is in fact able to provide flame retardant properties due to its intrinsically intumescent building blocks (deoxyribose, phosphoric-polyphosphoric acid and nitrogen-containing bases). In a first step, anchor groups (i.e. carboxyl groups) for subsequent coupling of DNA were introduced to PET and nylon-6 fabrics via limited surface hydrolysis with Humicola insolens cutinase (HiC). Released monomer/oligomers were measured via HPLC (1 mM of BHET for PET and 0.07 mM of caprolactam from nylon after 72 h). In a next step, DNA immobilization on the activated polymers was studied by using three different coupling systems, namely: EDC/NHS, dopamine and tyrosine. DNA coupling was confirmed via FT-IR that showed typical bands at 1220, 970 and 840 cm-1. The tyrosine/DNA coupling on nylon fabrics resulted to be the most effective as certified by the lowest burning rate and total burning time (35 s, 150 mm and 4.3 mm*s-1 for the blank and 3.5 s, 17.5 mm and 5 mm* s-1 for nylon/tyrosine/DNA) which was also confirmed by FT-IR and ESEM/EDS measurements. Thermogravimetric analysis (TGA) further confirmed that tyrosine/DNA coated nylon showed a lower thermal degradation between 450-625 °C when compared to the untreated samples.